The Phonological Interference of Students’ First Language in Pronouncing English Sounds (A Case Study on Buginese and Makassarese Students) - Dian Hera Utami; Muhammad Basri Wello; Haryanto Atmowardoyo (ELT Worldwide: Journal of English Language Teaching, 2017)
The study indicates the phonological interferences occurred by the Buginese and Makasserese students in pronouncing English sounds and the factors affect pronunciation interference of Buginese and Makasserese students in pronouncing English sounds. The respondents were eight university students majoring English Department. They are four Buginese students which their L1 is Buginese and four Makassarese students which their L1 is Makassarese. This research was conducted through a case study design. The instruments were oral test by reading three different texts to get the data with audio recording and interview about students’ problems in pronouncing English sounds. The result of data analysis showed that there is 46 kinds manner of articulation that the students made when they produced English sounds; 32 vowels and 14 consonants. The data also showed that the main factor that influences the students while pronouncing English words is interlanguage transfer. The implication of this research can be expected upon teaching and learning process. The students should put more awareness toward the L1 interference in pronouncing English vowels and consonant and drill more the correct pronunciation. The study also suggests that the teachers should give an extra attention to this problem. The teacher expected can help the students to reduce the mispronounced. The study also has some contributions to the language field where teachers/lecturers need to take a special attention of this phenomenon.